2016
DOI: 10.1007/s11682-016-9515-8
|View full text |Cite
|
Sign up to set email alerts
|

Decoding power-spectral profiles from FMRI brain activities during naturalistic auditory experience

Abstract: Recent studies have demonstrated a close relationship between computational acoustic features and neural brain activities, and have largely advanced our understanding of auditory information processing in the human brain. Along this line, we proposed a multidisciplinary study to examine whether power spectral density (PSD) profiles can be decoded from brain activities during naturalistic auditory experience. The study was performed on a high resolution functional magnetic resonance imaging (fMRI) dataset acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The dataset has, so far, been used to study the role of the insula in dynamic emotional experiences 2 , modeling of shared blood oxygenation level dependent (BOLD) response patterns across brains 3 , and to decode input audio power-spectrum profiles from fMRI 4 . The dataset has subsequently been extended twice, first with additional fMRI data from stimulation with music from various genres 5 and secondly with a description of the movie stimulus structure with respect to portrayed emotions 6 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The dataset has, so far, been used to study the role of the insula in dynamic emotional experiences 2 , modeling of shared blood oxygenation level dependent (BOLD) response patterns across brains 3 , and to decode input audio power-spectrum profiles from fMRI 4 . The dataset has subsequently been extended twice, first with additional fMRI data from stimulation with music from various genres 5 and secondly with a description of the movie stimulus structure with respect to portrayed emotions 6 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Using behavioral data about psychometric parameters as the supporting information, we attempted to test whether functional networks of the brain could be identified by rs-fMRI signals and psychological parameters (Figure 1 ). Recently some studies have shown that it is possible to decode brain states from fMRI responses using machine learning algorithms, such as a support vector machine (Guo et al, 2015 ; Altmann et al, 2016 ; Hu et al, 2017 ; Zafar et al, 2017 ). To verify that the functional networks identified represent the corresponding psychological parameters, and also to evaluate human characteristics from the rs-fMRI signals, we used a support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…It's been shown that single trial (i.e. without repetition) measurements during movie watching contain sufficient information to train successful decoding models (Hu et al, 2017) and that functional alignment across subjects based on such single trial measurements can improve decoding performance relative to single-subject decoding (Haxby et al, 2011, Bazeille et al, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 27, 2021. ; https://doi.org/10.1101/2021.01.26.428323 doi: bioRxiv preprint movie watching contain sufficient information to train successful decoding models (Hu et al, 2017) and that functional alignment across subjects based on such single trial measurements can improve decoding performance relative to single-subject decoding (Haxby et al, 2011, Bazeille et al, 2020. Experimental designs of this type sacrifice reliable responses to individual conditions in favor of maximizing the diversity of stimuli presented (which aids generalization) and the number of brain volumes collected.…”
mentioning
confidence: 99%